Inovação e propriedade intelectual: uma investigação no Porto do Itaqui - LOPES, Paulo Ricardo Gomes (2022)
Over the past decades ports have undergone profound transformations to meet market and regulatory demands. They have found in innovation a strategy to remain competitive and sustainable. The need to innovate has become a constant, turning ports into research, development, and innovation environments, making them potential catalysts for intellectual property. The present research was developed with the objective of investigating innovation at the Port of Itaqui with a focus on intellectual property. The research used a qualitative, exploratory approach, using bibliographic and documentary research and case studies as data collection tools. Intellectual property presents itself as a dynamic mechanism, simultaneously protecting and promoting innovation, favoring a virtuous cycle of development. The investigation showed that the Port of Itaqui, through its port authority, is the holder of a trademark and a computer program, with no results for the other categories of intellectual property. At first, the insignificant result would indicate a not very productive scenario. However, it was found that the Port of Itaqui brings together several initiatives aimed at port innovation, highlighting the creation of a Research, Development and Innovation Policy - RD&I, the articulation with various institutions for the creation of a port ecosystem in Maranhão and the project for the implementation of a port innovation center, making it stand out from other Brazilian public ports.